Non-thermal atmospheric plasma brush induces HEMA grafting onto dentin collagen - Chen, Mingsheng; Zhang, Ying; Dusevich, Vladimir; Liu, Yi; Yu, Qingsong; Wang, Yong (Dental materials, 2014)
•Non-thermal plasmas induce HEMA grafting onto dentin collagen under clinical settings.•Grafting efficacy of HEMA depends on the treatment time and input power of plasmas.•A new method to create chemical bond between resin monomers and dentin collagen. Non-thermal atmospheric plasma (NTAP) brush has been regarded as a promising technique to enhance dental interfacial bonding. However, the principal enhancement mechanisms have not been well identified. In this study, the effect of non-thermal plasmas on grafting of HEMA, a typical dental monomer, onto dentin collagen thin films was investigated. Human dentin was sectioned into 10-μm-thick films. After total demineralization in 0.5M EDTA solution for 30min, the dentin collagen films were water-rinsed, air-dried, treated with 35wt% HEMA aqueous solution. The films were then subject to plasma-exposure under a NTAP brush with different time (1–8min)/input power (5–15W). For comparison, the dentin collagen films were also treated with the above HEMA solution containing photo-initiators, then subject to light-curing. After plasma-exposure or light-curing, the HEMA-collagen films were rinsed in deionized water, and then examined by FTIR spectroscopy and TEM. The FITR results indicated that plasma-exposure could induce significant HEMA grafting onto dentin collagen thin films. In contrast, light-curing led to no detectable interaction of HEMA with dentin collagen. Quantitative IR spectral analysis (i.e., 1720/3075 or 749/3075, HEMA/collagen ratios) further suggested that the grafting efficacy of HEMA onto the plasma-exposed collagen thin films strongly depended on the treatment time and input power of plasmas. TEM results indicated that plasma treatment did not alter collagen's banding structure. The current study provides deeper insight into the mechanism of dental adhesion enhancement induced by non-thermal plasmas treatment. The NTAP brush could be a promising method to create chemical bond between resin monomers and dentin collagen.